Enhanced Production of Ethanol from Red Potatoes Grown in Hilly Regions of Nepal Using Various Nitrogen Sources - Joshi, Jarina (International Journal of Applied Sciences and Biotechnology, 2014)
Ammonium sulphate, ammonium phosphate, sodium nitrate, urea and glycine were the five different commonly available nitrogen sources used at different concentration ranging from 0.5 to 4% w/v to produce ethanol in batch culture. Potato paste made from red potatoes grown in hilly regions of Nepal was used as carbon source. Prior to fermentation all carbon sources were saccharified enzymatically using α- amylase at pH 5 and temperature 55oC. Maximum yield of ethanol 5.2% was obtained at a temperature of 30oC and pH 5.0 without exogeneous supply of nitrogen. There is slight decrease in concentration when temperature is decreased to 25oC but a drastic decrease in concentration when temperature is increased beyond optimum. All the exogeneously supplied nitrogen sources found to enhance ethanol production and cell viability when yeast strain Saccharomyces cerevisiae isolated from brewer’s yeast was used. Ammonium sulphate was found as best nitrogen supplement among them. Maximum ethanol percentage of 8.3 was observed at pH 5.0 and temperature 30oC with Ammonium sulphate concentration of 2%. DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.9191 Int J Appl Sci Biotechnol, Vol. 2(1): 41-44